Reduction of nitrogen fertilizer and simultaneously application of organic fertilizer optimizes yield, water productivity and nitrogen metabolism of spring maize by improving soil properties in the Loess Plateau of China - Fan Zhang; Mengru Chen; Yingying Xing; Juan Han; Xiukang Wang (Journal of Agriculture and Food Research)
Reduction of nitrogen fertilizer and simultaneously application of organic fertilizer (RNF) is regarded as an essential approach for realizing sustainable agricultural development. Nevertheless, studies on the effects of crop growth, N metabolism, water productivity, as well as the mechanisms by which soil factors regulate grain yield of spring maize under RNF conditions in the Loess Plateau of China, remain lacking. A three-year (2021, 2022, and 2023) field spring maize planting experiment with six treatments (no N fertilizer and organic fertilizer substituting 0 %, 12.5 %, 25 %, 37.5 %, and 50 % of chemical fertilizer N, respectively) was conducted using a randomized block design to study the effect of RNF on growth, yield, water productivity, and N metabolism of spring maize. The results showed that RNF conditions significantly improved crop growth characteristics and soil properties, with the most prominent at 25 % and 37.5 % substitution rate. Overall, the 25 % (37.5 %) substitution rate increased grain yield, net income, and water productivity by 72.11 % (73.24 %), 151.82 % (154.92 %), and 63.86 % (64.39 %), respectively, while optimizing nitrogen metabolism and soil properties compared with no N fertilizer application. Notably, soil microbial population and nitrate nitrogen residue significantly affected spring maize yield and may be important factors in monitoring yield variation. In summary, our study revealed the mechanism by which RNF regulated crop growth by improving soil properties, thereby increasing water productivity and N use efficiency, and ultimately increasing grain yield. Therefore, we suggest that RNF of 25 % and 37.5 % can be used in agricultural production, but continued use requires monitoring for variations in soil microbial population and nitrate nitrogen residue. This study serves as an important reference for the optimal management of N fertilizer and the promotion of sustainable agricultural development of spring maize cultivation in the Loess Plateau region of China.